Effectiveness of schema therapy on marital exhaustion, sexual self-efficacy and women's feeling of loneliness in the family - Nasirnia Samakoush, Alireza; Yousefi, Nasser (Psychology of Woman Journal, 2023)
Objective: The aim of the present study was to examine the effectiveness of schema therapy on marital burnout, sexual self-efficacy, and the feeling of loneliness in women within the family.Materials and Methods: This study was applied in nature and used a quasi-experimental method with a pretest-posttest control group design. Participants were randomly assigned to either the experimental or control group. The statistical population consisted of couples from the city of Sari who had sought counseling services there. A total of 30 individuals from this population were selected using random cluster sampling at the counseling centers of Sari city, from October 2021 to August 2022, based on predetermined criteria. For data collection, the Sexual Self-Efficacy Scale (Vaziri & Lotfi Kashani, 2013), the Loneliness Scale (Russell, Peplau, & Cutrona, 1980), and the Marital Burnout Questionnaire (Pines, 2003) were utilized. The current study employed descriptive statistics (mean and standard deviation) and inferential statistics (analysis of covariance).Findings: The results indicated that the coefficients related to the impact of schema therapy on marital burnout, sexual self-efficacy, and the feeling of loneliness in women within the family were significant at the 0.05 alpha level (p < 0.05). Thus, the research hypothesis regarding the effectiveness of schema therapy on marital burnout, sexual self-efficacy, and the feeling of loneliness in women within the family was confirmed.Conclusion: Based on the findings, schema therapy can be considered an effective treatment for reducing marital burnout, increasing sexual self-efficacy, and decreasing the feeling of loneliness in women within the family.